EFEK EKSTRAK BUAH KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP GAMBARAN HISTOPATOLOGI GINJAL PADA TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIINDUKSI STREPTOZOTOCIN - Sabian Bintang Ramadhan; Humairah Medina Liza Lubis (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
The prevalence of Diabetes Mellitus (DM) continues to increase globally, including in Indonesia, prompting research to explore natural compounds as alternative therapeutic agents. Oil palm (Elaeis guineensis Jacq.) has attracted attention because it contains antioxidant compounds. This study aimed to evaluate the effect of Elaeis guineensis fruit extract on renal histopathological changes in male Wistar rats (Rattus norvegicus) induced with streptozotocin as a diabetic model. This study used an in vivo experimental approach with a post-test only control design. The samples were divided into five groups: one positive control group, one negative control group, and three treatment groups receiving different doses of the extract. Observations were conducted at the post-test stage by comparing renal histopathological features among all groups. Data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test, with a significance level of p<0.05. Results showed significant differences between the positive control group and the negative control group, as well as with treatment group 2 (P2) and treatment group 3 (P3). The negative control group showed significant differences compared to treatment group 1 (P1) and treatment group 2 (P2). However, treatment group 3 (P3) did not show a significant difference compared to the negative control group. Significant differences were observed between P1 and P3 and between P2 and P3, while no significant difference was found between P1 and P2. In conclusion, Elaeis guineensis fruit extract demonstrated a positive effect in improving renal histopathological damage induced by streptozotocin, indicating its potential as supportive therapy in diabetes mellitus management.